Diminishing cooling effects of China’s largest freshwater lake due to shrinking water surfaces - Zhuoyu Li; Xiaosong Zhao; Xingwang Fan; Yanyu Lu; Lejun Zhao; Aoqi Wu (Ecological Indicators)
Cooling is an important ecosystem service provided by lakes, yet how its strength changes over time remains unclear, particularly for lakes sensitive to climate change. We assessed the cooling effects of China’s largest freshwater lake from 1980 to 2023. On average, the lake can cool the basin land within 60 km, reducing the respective annual mean air temperature (Ta) and apparent temperature (AT) by 0.37 °C and 0.86 °C. The daily maximum temperatures can be lowered by up to 3 °C. A regime shift has been observed since 2003, with the lake’s cooling effect weakening by 23 % for Ta and 29 % for AT, mainly due to shrinking water surfaces and reduced water storage. As a result, the capacity of heat storage and heat release has been impaired by 17% and 37%, respectively, weakening the lake’s thermal buffering role. Extreme events exert divergent impacts: the cooling effect persisted during drought years, but a warming effect occurred during flood years due to cloud cover suppressing evaporation. Our findings highlight how hydrological changes affect lake cooling and emphasize the value of lakes in reducing extreme heat in a warming climate.